A regulatory perspective on the evaluation of hallucinogen drugs for human use - Calderon, Silvia N.; Hunt, Joshua; Klein, Michael (Neuropharmacology, 2018)
In recent years, there is renewed interest in the study of various hallucinogens for their potential therapeutic effects. In the United States of America (USA), the abuse potential assessment of a drug is carried out as part of the general safety and efficacy evaluation of a drug. Additionally, the abuse potential assessment is taken under consideration in determining if a drug needs to be subject to controls to minimize the abuse of the drug once on the market. This assessment is conducted for all new drugs with central nervous system (CNS) activity, that are chemically or pharmacologically similar to other drugs with known abuse potential, or drugs that produce psychoactive effects predictive of abuse, such as euphoria and hallucinations. This paper describes the regulatory framework for evaluating the abuse potential of new drugs, with emphasis on hallucinogens. The paper discusses the role of the United States Food and Drug Administration (FDA) in the evaluation of the abuse potential of drugs and its role in drug control, and provides an overview of the controlled status of hallucinogens and the requirements to conduct research with Schedule I substances in the USA. This article is part of the Special Issue entitled ‘Psychedelics: New Doors, Altered Perceptions’. •The USA regulatory framework that applies to the development of hallucinogenic drugs is the same as for all other drugs.•The safety and effectiveness of a drug for its intended use must be demonstrated to approve the drug for marketing.•The abuse potential of a drug is one safety factor that needs to be evaluated.•Characterization of the abuse potential of a drug informs labeling, risk management strategies, and controls.•Some hallucinogens show promise in medical treatment; however, their overall safety and efficacy still need to be evaluated.